Anxiety as a cultural paradigm of social media: Instagram as an example - Đurđević, Marija (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2025)
Social media are one of the principal characteristics of contemporary, digital era. They have multiple roles – they are simultaneously a communication tool, communication space and a field for socialization and creation of meaning and value. The main hypothesis of this paper is that anxiety, although a term originating from philosophy, psychiatry, psychoanalysis and psychology, can be transposed into the domain of culturology and analyzed as a cultural topos. The second hypothesis is that anxiety understood as a cultural topos represents a cultural paradigm of social media. One of the most popular and widespread social media now is Instagram. Because of this, but also due to its specific functions and ideological background, we chose and analyzed this social network so as to demonstrate the workings of the culture of anxiety. We are of the opinion that such a view of anxiety could open up new perspectives on different aspects of the digital age we live in and point to the importance of developing critical apparatus and media literacy in users of new digital platforms.